Viable Sweetpotato Technologies for Africa (VISTA) Project Mozambique - International Potato Center (2017)
In 2017, 16,500 households received a total of 132 tons of diseasefree planting material. We trained 427 community health workers on improved child feeding practices and a better diet for mothers, and other relevant nutritional and dietary topics. About 6,000 families were reached with nutrition training in Nampula and Zambézia provinces.